Textile engineering : an introduction - Nawab, Yasir (De Gruyter textbook., 2016)
"Currently, most of the textile industry and textile institutions are located in South Asia. The textile industry leads to the development of clothing from fibres, yarns, and fabrics. The industry is growing in this area as it has already been shifted from Europe and is being shifting from China. As the textile industry is growing, many new textile intuitions are being established to provide for quality textile education. This introductory level textbooks is geared towars them. This book will provide all necessary information from fibres to fabrics and their conversion to clothing. The importance of textiles in the current era along with the raw materials needed for the textiles are given. After that, it is explained how the yarn is made from fibres. Then the fabrics manufacturing, the printing and dyeing of textiles and the conversion of fabrics into the garments is discussed. Also, the testing of fibres, yarns and fabrics along with the description of technical textiles is mentioned. This book is beneficial for all readers who are going to start their career in textiles or are going to start the engineering degree in textiles. The present book is designed for the first year students (especially for the National Textile University Faisalabad) of textile engineering."